PENGARUH TUNJANGAN KINERJA, PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI DENGAN KEPRIBADIAN PEGAWAI SEBAGAI VARIABEL MODERASI : Studi Kasus di Kantor Pelayanan Pajak Pratama Wates (Jurnal Riset Manajemen Akuntansi Indonesia, 2024)
This research aims to analyze the impact of performance allowances, career development on employee performance with employee personality as a moderating variable at the Wates Primary Tax Service Office. This research uses a quantitative descriptive approach. Data collection was done using the questionnaire method and data analysis was tested using Smart PLS 3.2.9 software. The population in this research is all employees of KPP Pratama Wates. Sampling is done by saturated sampling method. The sample in this research is KPP Pratama Wates employees as many as 82 employees. The results of this research prove that performance allowance has a positive and significant effect on employee performance, career development has a positive and significant effect on employee performance, employee personality has a positive and significant effect on employee performance, employee personality is able to moderate the effect of performance allowance on employee performance, employee personality is able to moderate the impact of career development on employee performance.
Keywords: Performance Allowance; Career Development; Employee Performance; Employee Personality